Вплив ші на право людини на недоторканність приватного життя та захист даних - Янакаєв, А. А. (ХНУРЕ, 2023)
The artificial intelligence (AI) development is being noticed more and more nowadays. It’s clear that now it comes closer than we could expect to life of everyone of us. Human rights are not an exception - as it turned out there are so many ways for AI to touch them. The Ukraine legal system is yet to define the artificial intelligence, but there are already a lot of incidents both inside and outside our country.